Comercial Mosi de Rltda - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1987)
SPANISH: Se observo la fachada del comercial Mosi de Rlda tambien se puede ver sus letreros donde oferece sus productos tanto de ferreteria como quimicosen la calle Arica cuadra 5 claramente una casona de la epoca del caucho.
ENGLISH: We observed the facade of the commercial Mosi de Rlda also you can see their signs where they offer their products both hardware and chemicals in the street Arica block 5 clearly a large house of the rubber era.

SPANISH: Se observo la fachada del comercial Mosi de Rlda tambien se puede ver sus letreros donde oferece sus productos tanto de ferreteria como quimicosen la calle Arica cuadra 5 claramente una casona de la epoca del caucho.
ENGLISH: We observed the facade of the commercial Mosi de Rlda also you can see their signs where they offer their products both hardware and chemicals in the street Arica block 5 clearly a large house of the rubber era.
Commercial Mosi de Rltda
Keywords: Iquitos (Perú)|~|Comercio|~|Perú|~|local comercial y negocio|~|comercio|~|Iquitos (Peru)|~|Commerce|~|Peru|~|business premises and business|~|trade|~|commerce